The encyclopedia of war - Martel, Gordon (Wiley-Blackwell, 2012)
This ground-breaking 5-volume reference is a comprehensive print and electronic resource covering the history of warfare from ancient times to the present day, across the entire globe. Arranged in A-Z format, the Encyclopedia provides an overview of the most important events, people, and terms associated with warfare - from the Punic Wars to the Mongol conquest of China, and the War on Terror; from the Ottoman Sultan, Suleiman 'the Magnificent', to the Soviet Military Commander, Georgi Konstantinovich Zhukov; and from the crossbow to chemical warfare.